Indoor monitoring with BLE in smart home - Teo, Sophin Shi Min (2018)
In recent years, due to many fast-paced technological advancements, people around the world expect a better quality of life. In a small country state like Singapore, it is especially important for us to make use of our resources and technology to create a better life for ourselves. The Smart Nation initiative encourages having meaningful and fulfilled lives through advancement in technology. One category at the forefront of this initiative is “Living”. With sparse and limited land, it is imperative that we constantly think of ways to make our living environment a better place to be in. Smart Home solutions come into play when we feel a need to improve our surroundings – and one of the most well-known technologies when Smart Homes are mentioned is Bluetooth Low Energy (BLE). BLE is known for its low power consumption, and has sparked much interest due to its power efficiency. This thesis presents a brief overview of the BLE technology, and how we can use the BLE technology to be implemented in a Smart Home setting. A Smart Home application will be set up, with a central information hub consolidating valuable data from different sensor nodes to optimise our surroundings. Moving forward, this thesis also explores the possibilities of BLE in future and hopes to provide insight into the BLE technology.